Preparation and Characterization of Novel Plaster with Improved Thermal Energy Storage Performance - Jan Fořt; Radimír Novotný; Anton Trník; Robert Černý (Energies, 2019)
Thermal energy storage systems based on latent heat utilization represent a promising way to achieve building sustainability and energy efficiency. The application of phase change materials (PCMs) can substantially improve the thermal performance of building envelopes, decrease the energy consumption, and support the thermal comfort maintenance, especially during peak periods. On this account, the newly formed form-stable PCM (FSPCM) based on diatomite impregnated by dodecanol is used as an admixture for design of interior plasters with enhanced thermal storage capability. In this study, the effect of FSPCM admixture on functional properties of plasters enriched by 8, 16 and 24 wt.% is determined. On this account, the assessment of physical, thermal, hygric, and mechanical properties is done in order to correlate obtained results with applied FSPCM dosages. Achieved results reveal only a minor influence of applied FSPCM admixture on material properties when compared to negative impacts of commercially produced PCMs. The differential scanning calorimetry discloses variations of the phase change temperature, which ranging from 20.75 °C to 21.68 °C and the effective heat capacity increased up to 15.38 J/g accordingly to the applied FSPCM dosages.